Deoximation of Ketoximes to Ketones with Ammonium Chlorochromate/Montmorillonite K10 in Dichloromethane - Ji-Tai Li; Xian-Tao Meng (E-Journal of Chemistry)
A convenient, mild and efficient method for oxidative cleavage of ketoximes to their parent carbonyl compounds with ammonium chlorochromate (ACC) / montmorillonite K10 in dichloromethane at room temperature is described